Farmers Behavior Towards Horticultural Plant Disease Infections in Bangka Regency - Lesta Lesta; Riski Meliya Ningsih; Priestiani Priestiani; Rindi Renanda (Program Studi Agroteknologi Universitas Siliwangi, 2026)
This study explores the knowledge, attitudes, and practices of farmers in Bangka Regency, Indonesia, regarding the management of diseases affecting horticultural crops. Field surveys and structured interviews were conducted across nine villages to assess the incidence of plant diseases and the control methods employed by local farmers. The results showed an average disease incidence of 23.33%, with the highest observed in cucumber crops at 66%. Most farmers (75%) practiced monoculture farming, which contributed to the persistence and spread of soil-borne diseases such as Fusarium wilt and root rot. Synthetic pesticides were the predominant control method, with 68% of farmers applying them regularly, and many exceeding recommended dosages. Although most respondents could visually identify disease symptoms, their understanding of disease development stages, causal agents, and sustainable control options was limited. Notably, none of the farmers were familiar with biological control agents and only a minority believed that organic materials could reduce disease incidence. The findings underscore a heavy dependence on chemical control and highlight a significant gap in awareness of integrated and environmentally friendly disease management practices. Factors such as improper pesticide use, poor seed quality, and suboptimal soil conditions further exacerbated disease risks. To enhance productivity and sustainability, it is critical to strengthen farmers' capacity through education and training in integrated disease management, emphasizing crop rotation, balanced fertilization, and the adoption of biological control strategies. These interventions are essential for reducing losses and promoting sustainable horticultural production in Bangka Regency.